POWAINDv1.0: A Program for Protein-Water Interactions Determination - Banerjee, Sahini (Bioinformation, 2018)
Protein is the most exposed biomolecule in the aqueous environment of the cell. Its structure maintains a delicate balance between the rigidity and the flexibility that imparts binding specificity to its substrate/ligand, etc. Intramolecular interactions of polar and non-polar groups of amino acid residues and intermolecular weak interactions between these groups and shell-waters may contribute to the overall stability of the tertiary structure. However, the question as to what are the dynamics of interactions of shell-water with respect to weak forces and atom-groups of protein (AGP), requires systematic investigations. In this end, we have developed a procedure POWAINDv1.0 that analyzes interactions of crystallographic shell-waters (CSH) in residues and AGP specific manner. The shell-water and AGP specific bridge-interactions are also extracted. Further, the program analyzes favorable and unfavorable nature of each interaction based on the actual and 75% of the sum of van der Waals (vdW) radii of interacting atoms. The EXCEL-outputs are useful in understanding the profile for AGP-CSH interactions and contribution of each component in AGP. Taken together, the program provides intricate details on CSHprotein interactions and finds application in the structural Bioinformatics